2001
DOI: 10.1111/j.1749-6632.2001.tb02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Prophylaxis and Therapy for Flavivirus Encephalitis Infections

Abstract: The outbreak of West Nile (WN) encephalitis in the United States has rekindled interest in developing direct methods for prevention and control of human flaviviral infections. Although equine WN vaccines are currently being developed, a WN vaccine for humans is years away. There is also no specific therapeutic agent for flaviviral infections. The incidence of human WN virus infection is very low, which makes it difficult to target the human populations in need of vaccination and to assess the vaccine's economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 53 publications
(104 reference statements)
3
93
0
1
Order By: Relevance
“…In our study, we found six different strongly neutralizing MAbs against DENV-2 that localized to two overlapping structural epitopes on the lateral ridge and adjacent A strand of DIII. For flaviviruses, virus type-specific epitopes generally elicit the most potent neutralizing antibodies (2,28,42,53,56,63,64). Of the DIII-specific MAbs against DENV-2 in our panel, in general, the ones with the strongest neutralizing activities were type specific and localized to the lateral ridge of DIII centered at the FG loop, near residues E383 and P384.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, we found six different strongly neutralizing MAbs against DENV-2 that localized to two overlapping structural epitopes on the lateral ridge and adjacent A strand of DIII. For flaviviruses, virus type-specific epitopes generally elicit the most potent neutralizing antibodies (2,28,42,53,56,63,64). Of the DIII-specific MAbs against DENV-2 in our panel, in general, the ones with the strongest neutralizing activities were type specific and localized to the lateral ridge of DIII centered at the FG loop, near residues E383 and P384.…”
Section: Discussionmentioning
confidence: 95%
“…Serotype-specific epitopes elicit antibodies with the strongest neutralizing activities (62,63), and protection in animals by antibodies correlates with neutralizing activity in vitro (6,20,25,43,53,63). Based on epitope mapping data, many type-specific neutralizing antibodies against individual flaviviruses localize to DIII (1,2,10,18,39,53,61,65,66,76), whereas neutralizing monoclonal antibodies (MAbs) that cross-react with other flaviviruses localize primarily to DII, near the fusion peptide (17,23,24,54,61,68).…”
mentioning
confidence: 99%
“…Mice deficient for B cells and antibody production demonstrated higher viral loads in CNS and increased vulnerability to lethal WNV infection than wild-type mice [221]. Similarly, adoptive transfer of monoclonal antibodies protected mice from lethal encephalitis caused by other flaviviruses, namely JEV [223], SLEV [224], and yellow fever virus [225]. Further, high levels of JEV-specific IgM and IgG in the CSF was linked to virus clearance from the CNS and a better clinical outcome in patients [226,227].…”
Section: Viral Clearance From the Cnsmentioning
confidence: 99%
“…However, recurring outbreaks in countries like India underline the need for a more effective vaccine (Kabilan et al, 2004;Parida et al, 2006). Studies carried out in humans and in animal models of the disease have indicated the importance of an effective humoral response in preventing flavivirus infection both in the periphery and within the central nervous system (CNS) (Burke et al, 1985;Roehrig et al, 2001;Ben-Nathan et al, 2003;Diamond et al, 2003).…”
Section: Introductionmentioning
confidence: 99%